'You're changing the subject': An unfair objection to conceptual engineering? - Belleri, Delia (Philosophical Quarterly, 2025)
Conceptual engineering projects are sometimes criticized for 'changing the subject'. In this paper, I first discuss three strategies that have been proposed to address the change of subject objection. I notice that these strategies fail in similar ways: they all deploy a 'loose' notion of subject matter, while the objector can always reply deploying a 'strict' notion. Based on this, I then argue that at least current formulations of the change of subject objection (together with the response strategies just mentioned), create an overall defective dialectic , whereby no progress can be made on either side. After considering how such defective dialectic could be (at least partly) fixed, it is concluded that current formulations of the change of subject objection may be dismissed on dialectical grounds , even though some practical lessons may still be retained from the objection.